Phytochemical screening and in vitro antimicrobial activity of Rosmarinus officinalis leaves - Christophe Nsanzamahoro; Emmanuel Gatozi; Jean Damascene Urimubenshi; Jean Ntaganda (BIORE Scientia Publisher, 2024)
Rosmarinus officinalis is a medicinal plant, which belongs to family Lamiaceae. It is an evergreen bush. It was analyzed for its phytochemical constitution and antibacterial activity. For this purpose, leaves of n-hexane, ethyl acetate and methanolic extracts were used. The tests of phytochemical screening showed that the plant leaves contain anthraquinones, terpenoids, flavonoids, reducing sugars, saponins, cardiac glycosides, coumarins, phenols, carbohydrates, proteins, steroids, alkaloids and quinones, while tannin was absent. The antibacterial activity was determined against E. coli and staphylococcus aureus; the invitro antibacterial activity was performed by disc diffusion method. The n-hexane and ethyl acetate extracts showed no antibacterial activity against E. coli while ethyl acetate extracts showed antibacterial activity against Staphylococcus sp. The results showed that the highest mean inhibition zone was observed in the methanolic extracts.